Drying Of Microalgae Chlorella Sorokiniana on Antioxidant Activity and Formulation Application on Peel Off Gel Masker - Mursandi, Hamza; Hendrawati, Tri Yuni; Budiyanto, Budiyanto (Journal of Applied Sciences and Advanced Technology, 2024)
Unhealty environmental conditions due to air pollution can cause the emergence of free radicals. Peel off gel mask is very practical and easy to apply mask by applaying evenly on the face and after draying, the mask can be removed immediately without the need to rinse. An alternative that can be chosen and is safe in overcoming skin problems is to use natural active inggridients, such as microalgae. Chlorella sorokiniana has nutritional conten, such as water content (6.54%), carbohydrates (18.08%), protein (46,80%), fat (19.93%), and minerals (7.3%). In addition, bioactive compound such as alkaloids, flavonoids, phenolics, saponins, and terpenoids. The purpose of this study was to dry microalgae C. sorokiniana at the best drying time conditions, testing proximate and bioacrtive compounds, such as total phenolics, flavonoids, and antioxidant activity, as well as formulating and evaluating C. sorokiniana microalgae powder mask preparations. The independent variabels in this study include the drying time of microalgae biomass C. sorokiniana 30, 60, 90, 120, and 150 minutes, as well as the concentration of microalgae powder C. sorokiniana 5, 10, 15, 20, 25% for the application of peel off gel mask preparations, while the dependent variables in this study include proximate content, total phenolic, total flavonoid, antioxidant activity, and evaluation of mask preparations. The procedures in this study include: cultivation, harvesting, and collection of microalgae biomass, drying process with time variations, proximate testing and bioactive compounds, as well as formulation and evaluation of C. sorokiniana microalgae powder mask preparations. The results showed that the best drying time for C. sorokiniana microalgae was 120 minutes with a constant drying rate. In proximate testing, including water content (9.27%), ash (4.28), carbohydrates (10.67%), fat (7.56%), protein (31.39%), and crude fiber (0.25%) which shows that the nutritional content of microalgae C. sorokiniana is quite high which can be used to nourish the skin. In addition, the total phenolic content (24.30 mgGAE/g), total flavonoids (19.70 mgQE/g), and antioxidant activity (543.79 mg/L) which shows the antioxidant content is very weak. In the evaluation of masks, organoleptic, pH, homogeneity, spreadability, dry time, and hedonic tests were carried out with 5 different formulations. Based on the evaluation results, the 4th formula has a formulation that meets the requirements and a high level of liking.